Body Tubes and Synaesthesia (2017)
The flows through tubular forms in the body, material culture and the natural environment play a key role in the thought of the indigenous peoples of Northwest Amazonia. Using examples from daily life, mythology and ritual, this paper examines the tube as an abstract concept that unites physiology, psychology, and productive processes with wider sociological and cosmological issues. The material, visual, and acoustic manifestations of tubular flow (hair) also raise the issues of synaesthesia and fractal notions of totalization / detotalization. With tubes as tantamount to life itself, ritual attention is focused on regulating bodily and other apertures to ensure balanced, tempered flow. The paper concludes by suggesting that the cultural elaboration of tubes and synaesthesia in Northwest Amazonia may relate to the lineal, exogamic features of social structure characteristic of the region.